Strengthening indigenous knowledge systems through research and extension linkages the Arakan Valley Complex experience - Maganaka, Albert M. (Danyag :the UPV journal of humanities and social sciences, 2000)
"This paper examines the value and practicality of incorporating indigenous knowledge components in agricultural research to augment sustainable development that benefits the upland rice farmers of Arakan Valley. It presents the efforts of development-oriented non-government organization in promoting community-based conservation per se and in affecting change and development in marginalized farming communities through research and extension mechanism."